An assessment of microplastic inputs into the aquatic environment from wastewater streams. (November 2020) - Uddin, Saif; Fowler, Scott W.; Behbehani, Montaha
Abstract: Wastewater treatment plants (WWTPs) play a pivotal role in removal of microplastics (MPs) particles before the waste streams are discharged into aquatic environments. Indiscriminate disposal of the effluent and untreated wastewater not only contribute to accumulation of MP in the marine environment, but they can also act as a carrier for various hydrophobic compounds and contributors of pollutants that leach from them via natural degradation. In this assessment, we have summarized the MP concentrations in influent and effluent streams, and provide quantification of the discharges from these WWTPs. Almost 50% of the global wastewater influent of 3, 562, 082 × 10 5 m 3 remains untreated. Some conservative estimates indicate that treated effluent disposal can add around 1.47 × 10 15 MPs annually, whereas the discharge of untreated effluent is likely to add a staggering 3.85 × 10 16 MPs annually to the aquatic environments. The efficiency of MP removal in wastewater treatment plants varies between 88 and 99.9%, indicating the potential of capturing the majority of the MP from escaping into the freshwater and marine environment. Based on WWTP removal efficiencies for MPs, calculations suggest that if all the globally produced wastewater was treated prior to release, a reduction of over 90% of the current amount of MP inputs into the aquatic environment could be achieved. From the number of studies conducted and assessments made on MPs in waste streams, it is obvious the methodologies followed were quite different, and the use of acids and heating are likely to deteriorate the MPs, emphasizing the need to develop harmonized protocols for microplastic assessment in wastewater treatment plants. Highlights: Wastewater treatment plants are the major pathway for microplastic input into aquatic environments. The MP removal efficiency of WWTPs varies between 88 and 99.9%. Treated and untreated effluent discharges are likely to contribute over 3.85 × 10 16 MPs a year.